Monitoração de requisitos de qualidade baseada na arquitetura de software - Silva, André Almeida (2015)
Computer systems gain more space day by day in the lives of individuals, causing the demand for computerized solutions more and more sophisticated and accurate, become increasing. Thus, there is a requirement of effective quality assurance for software produced, checked by monitoring of quality attributes. However, the main current monitoring techniques are turning mainly to service-based systems, setting aside a large number of software. In this context, this work aims to discuss about the monitoring of quality attributes referenced by ISO/IEC 9126 standard. Decision trees will be set relating to the architectural elements monitoring issues, and also a tool that uses the concepts of Aspect-Oriented Programming to automate the process of monitoring the reliability and efficiency requirements by generating aspects-monitors intended for logging and recording exceptions given target system. Still be observed the case study disposal structured by the Goal/Question/Metric (GQM) paradigm, conducted with the purpose of analyze the feasibility of the developed solution which is a simplified way for architects and software developers to define monitors to measure quality attributes in their systems.